Quality of environmental disclosure of environmentally sensitive industries in Malaysia - Norhayati binti Abdullah (International Islamic University Malaysia, International Islamic University Malaysia, 2011)
The Malaysian government is becoming increasingly concerned about the corporate environmental policies regulating the Malaysian companies. As a result, Bursa Malaysia, as an authoritative body in monitoring the Malaysian PLCs, has made it mandatory for all listed companies in Malaysia to publicly disclose their social and environmental related information in annual reports effective year 2007 onwards. Better quality environmental disclosures may indicate that corporations place their contribution and commitment in effort to protect the environment. The purpose of this study is thus to examine the quality of environmental disclosure in annual reports after the mandatory requirement took place. Furthermore, it also aims to identify determinants of the quality of environmental disclosure using multi-theoretical perspectives that rely on institutional theory, information cost theory, resource based view theory and legitimacy theory. The study compared the quality of environmental disclosures between year 2005 and 2009; before and after the CSR mandatory reporting requirement that took effect in Malaysia. The quality of environmental disclosures was measured using a disclosure index. A content analysis of the annual report of 164 environmentally sensitive industries companies was undertaken. The findings reveal that there is a significant increase in the quality of environmental disclosures in 2009 as compared to 2005. Accordingly, the study concludes that the environmental reporting in Malaysia is now improving as compared to years before the mandatory requirement. Theoretically, the findings suggest that the better quality environmental disclosures in annual reports by corporations in 2009 may well be influenced by the mandatory CSR requirement. Additionally, the results also suggest the quality of environmental disclosures in Malaysia is determined by firms' size and leverage level. This result is strongly supported by legitimacy theory. Overall, the study views institutional and legitimacy based theoretical perspectives as complementary in providing an appropriate explanation for environmental reporting behaviour in Malaysia.